Study of Energy Transfer in the Photosynthetic Process: A Quantum Mechanical Approach (2025)
In this work, energy transfer in the photosynthetic process was studied from a quantum perspective, using the Fenna–Matthews–Olson (FMO) complex as a model. The density operator formalism and the Lindblad master equation were employed to describe the non-unitary dynamics of an open system subject to injection, extraction, and decoherence processes. A two-level system and a three-site FMO complex were analyzed, allowing the study of phenomena such as Rabi oscillations, environment-induced coherence loss, and the emergence of Environment-Assisted Quantum Transport (ENAQT). Through numerical simulations, exciton and heat currents, von Neumann entropy, global and intersite entanglement, and energy transfer efficiency were calculated. The results show that, far from being an obstacle, the interaction with the environment can enhance photosynthetic efficiency under intermediate noise regimes, thus validating the ENAQT hypothesis. This study confirms that photosynthetic systems exploit a delicate balance between coherence and decoherence to optimize energy transport.